Inflammatory Response of Ischemic Tolerance in Circulating Plasma: Preconditioning-Induced by Transient Ischemic Attack (TIA) Phenomena in Acute Ischemia Patients (AIS) - Colàs-Campàs, Laura; Farre, Joan; Mauri-Capdevila, Gerard; Molina-Seguín, Jessica; Aymerich, Núria; Ois, Ángel; Roquer, Jaume; Tur, Silvia; García-Carreira, María del Carmen; Martí-Fàbregas, Joan; Cruz-Culebras, Antonio; Segura, Tomás; et al. (Frontiers in Neurology, 2020)
Introduction: Ischemic tolerance (IT) refers to a state where cells are resistant to the damaging effects caused by periods of ischemia. In a clinical scenario, the IT phenomenon would be activated by a recent transient ischemic attack (TIA) before an ischemic stroke (IS). The characterization of inflammatory protein expression patterns will contribute to improved understanding of IT. Methods: A total of 477 IS patients from nine hospitals, recruited between January 2011 and January 2016, were included in the current study and divided in three groups: 438 (91.9%) patients without previous TIA (group 1), 22 (4.6%) patients who suffered TIA 24 h before IS (group 2), and 17 (3.5%) patients who suffered TIA between 24 h and 7 days prior to IS (group 3). An inflammatory biomarker panel (IL-6, NT-proBNP, hsCRP, hs-Troponin, NSE, and S-100b) on plasma and a cytokine antibody array was performed to achieve the preconditioning signature potentially induced by TIA phenomena. Primary outcome was modified rankin scale (mRs) score at 90 days. Results: Recent previous TIA was associated with better clinical outcome at 90 days (median mRS of group 1: 2.0 [1.0–4.0]; group 2: 2.0 [0.0–3.0]; group 3: 1.0 [0–2.5]; p = 0.086) and smaller brain lesion (group 1: 3.7 [0.7–18.3]; group 2: 0.8 [0.3–8.9]; group 3: 0.6 [0.1–5.5] mL; p = 0.006). All inflammation biomarkers were down regulated in the groups of recent TIA prior to IS compared to those who did not suffer a TIA events. Moreover, a cytokine antibody array revealed 30 differentially expressed proteins between the three groups. Among them, HRG1-alpha (Fold change 74.4 between group 1 and 2; 74.2 between group 1 and 3) and MAC-1 (Fold change 0.05 between group 1 and 2; 0.06 between group 1 and 3) expression levels would better stratify patients with TIA 7 days before IS. These two proteins showed an earlier inflammation profile that was not detectable by the biomarker panel. Conclusion: Inflammatory pathways were activated by transient ischemic attack, however the period of time between this event and a further ischemic stroke could be determined by a protein signature that would contribute to define the role of ischemic tolerance induced by TIA.